Migrating football players, transfer fees and migration controls - Harrie A. A. Verbon (Center for Economic Studies and ifo Institute (CESifo), 2007)
Since the famous Bosman ruling by the European Court of Justice in 1995 transfer fees for football players after moving to another club have become suspect as they are considered as an obstacle to the free movement of workers. However, in an unrestricted market free migration from football players will be Pareto efficient under special circumstances only. This paper shows that transfer fees can correct inefficient migration flows from small to large football leagues. Home-grown rules that prescribe that a certain proportion of the roster of players should be trained within the club are very blunt devices for restoring efficiency, and perform worse than transfer fee systems.
Keywords: H77; J61; L83; 330; Fußballsport; Professioneller Sport; Sportler; Arbeitsmobilität; Internationale Arbeitsmobilität; Pareto-Optimum; Theorie